The effects of exercise intensity on the gut microbiota of college basketball players - Deng, Hong-xian; Li, Huan-huan; Qiao, Jiu-quan; Tong, Yan; Wang, Cui-juan; Liu, Jiang (Journal of Community Medicine and Health Solutions, 2023)
Purpose: Exercise has a positive regulatory effect on gut microbiota and is also involved in regulating multiple physiological functions of the human body. This article tested the effects of basketball exercises at different exercise intensities on the gut microbiota of college students. Methods: Athlete research subjects (male, aged 18 - 25) were selected from the basketball team and trained at different intensities to obtain a total of 101 fresh fecal samples. DNA was extracted by a DNA extraction kit and bacterial 16S rRNA gene V3-V4 region high-throughput sequencing using the Illumina Hiseq platform. The downstream data were spliced, filtered and de-trimerized and then used to study the difference in gut microbiota. Results: Key bacterial taxa in the gut that responded to exercise intensity differed among athletes of different exercise intensities but most belonged to Firmicutes. With increasing exercise intensity, Butyricicoccus, Anaerostipes, Oxalobacter and Clostridium_IV in basketball players enrich. Further analysis of the functional prediction revealed that carbohydrate metabolism, amino acid metabolism, metabolism of xenobiotics and glycans and metabolism were significantly expressed in the gut microbiota of basketball athletes with high intensity. Conclusion: The study demonstrated that after long-term professional training, the gut microbiota of athletes adapts to exercise stimulators and can quickly respond to changes in exercise intensity. In high-intensity training, the organism is protected from harm by enriching some beneficial bacteria.